Hybrid mobility prediction of 802.11 Infrastructure nodes by location Tracking and data mining - Biju, Issac; Khairuddin, Ab Hamid; C.E., Tan (Journal of IT in Asia, 2010)
In an IEEE 802.11 Infrastructure network, as the mobile node is movingfrom one access pointto another, the resource allocation and smooth hand offmay be a problem. Ifsome reliable prediction is done on mobile node's next move, then resources can be allocated optimally as the mobile node moves around. This would increase the performance throughput ofwireless network. We plan to investigate on a hybrid mobility prediction scheme that uses location tracking and data mining to predict thefuture path ofthe mobile node. We also propose a secure version ofthe same scheme. Through simulation and analysis, we present the prediction accuracy ofour proposal.